Narrative Review: Optimasi Etanol sebagai Pelarut Senyawa Flavonoid dan Fenolik - Ali Rakhman Hakim; Rina Saputri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The use of ethanol as a solvent for secondary metabolite compounds is very widespread. Ethanol can dissolve flavonoid compounds and phenolic compounds from plants. To be able to utilize ethanol as a solvent is dependent on some factors of concentration, temperature, time, and selection of extraction methods. This study uses the method by searching scientific articles from the MDPI website database. The Ultrasound-Assisted Extraction (UAE) method is very suitable for the optimization of ethanol as a solvent. The optimal use of ethanol is in the concentration range of 50-80%, temperature conditions in the range of 40-70ºC, and the extraction time is in the range of 30 minutes - 24 hours.